Crimes of art + terror - Lentricchia, Frank (University of Chicago Press, 2003)
Do killers, artists, and terrorists need one another? The authors explore this question through the disturbing adjacency of literary creativity to violence and even political terror anchoring the discussion on the aftermath of the destruction of the World Trade Center.